ANALISIS YURIDIS TERHADAP PASAL 27 AYAT 3 UNDANG-UNDANG NOMER 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK DIKAITKAN DENGAN HAK ASASI MANUSIA - Sinaga, Lusya Ermauli Br; Effendi, Erdianto; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Freedom of expression is a fundamental part of human rights. In addition to international recognition through the Universal Declaration of Human Rights (DUHAM) of 1948 or Universal Declaration of Human Rights, also nationally Indonesia is very insistent mention of freedom of expression in the Constitution of 1945. In Article 28E Paragraph (3) of the 1945 Constitution which states, "Everyone has the right to freedom of association, assembly, and expression". The right includes freedom of opinion without interruption, sertamari, receiving, and forward all information and ideas, through any media and regardless of the limit ". Freedom of expression and expression is a Universal principle in a democratic state.Freedom of expression and association is another absolute requirement, which a State of Democracy must possess. This freedom must be guaranteed also in the law of the State concerned. The relevant State Law regulating freedom of expression and association shall expressly express freedom of expression both orally and in writing. Based on the above discussion, the authors raised the title "Analysis of Judicial Review Against Article 27 paragraph 3 of Law Number 19 Year 2016 About Information and Transactions Electronics Associated With Human Rights". The ITE Act does not limit the freedom of expression of some of the acts prohibited in Article 27 but, limiting that freedom to avoid harming others, is related to the distribution of transactions involving the violation of decency (including porno-grafy), gambling, humiliation, defamation, extortion , threats. (3) Every Person intentionally and without right to distribute and / or transmit and / or make accessible Electronic information and / or Electronic Documents with defamatory and / or defamatory content "This type of research, the authors use the type of normative research. Normative research is literature law research, where in normative law research the literature is basic data which in research is classified as secondary data. The secondary data has a wide scope, covering personal letters, diaries, books, and official documents issued by the government.Keywords: Yuridical Analysis - Information and Electronic Transactions - Human Right